Penicillium italicum: An Underexplored Postharvest Pathogen - Aline Midori Kanashiro; Daniel Yuri Akiyama; Katia Cristina Kupper; Taícia Pacheco Fill (Frontiers in Microbiology, 2020)
In the agricultural sector, citrus is one of the most important fruit genus in the world. In this scenario, Brazil is the largest producer of oranges; 34% of the global production, and exporter of concentrated orange juice; 76% of the juice consumed in the planet, summing up US$ 6.5 billion to Brazilian GDP. However, the orange production has been considerable decreasing due to unfavorable weather conditions in recent years and the increasing number of pathogen infections. One of the main citrus post-harvest phytopathogen is Penicillium italicum, responsible for the blue mold disease, which is currently controlled by pesticides, such as Imazalil, Pyrimethanil, Fludioxonil, and Tiabendazole, which are toxic chemicals harmful to the environment and also to human health. In addition, P. italicum has developed considerable resistance to these chemicals as a result of widespread applications. To address this growing problem, the search for new control methods of citrus post-harvest phytopathogens is being extensively explored, resulting in promising new approaches such as biocontrol methods as “killer” yeasts, application of essential oils, and antimicrobial volatile substances. The alternative methodologies to control P. italicum are reviewed here, as well as the fungal virulence factors and infection strategies. Therefore, this review will focus on a general overview of recent research carried out regarding the phytopathological interaction of P. italicum and its citrus host.